Analisis Strategi Pemasaran Dan Pengelolaan Usaha Pada UMKM D Kopi Paste Di Kota Padang - Amir Rabbani Awwab; Aisyah Salsabila; Jelita Amelia; Sularno .; Novadilastri . (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Micro, small, and medium enterprises (MSMEs) in the contemporary coffee culinary sector are growing rapidly in Padang City, yet many business owners have not systematically evaluated whether their marketing and operational strategies are truly aligned with the perceptions actually experienced by consumers in the market. This study aims to analyze, describe, and deeply understand the marketing strategy and operational management of the D Kopi Paste MSME in Padang City, from both the internal perspective of the owner and the external perspective of customers, in order to assess the level of synchronization between the two. The study employs a descriptive qualitative approach using semi-structured interviews with one business owner and three customers of D Kopi Paste, located in front of the Al Minangkabawi Mosque, Padang City. Data were analyzed through thematic analysis involving data reduction, data display, and conclusion drawing, strengthened by source triangulation between the owner's and customers' responses. The findings show that D Kopi Paste's marketing strategy relies on digital promotion through social media (Instagram and TikTok) combined with word-of-mouth strategy, as well as product differentiation based on premium quality at an affordable price. Operationally, the owner emphasizes the selection of quality raw material suppliers and fast, friendly service as competitive advantages amid intense competition from mobile coffee vendors, primarily through price adjustment strategies. Findings from the three customers show a high degree of conformity between the owner's internal claims and the actual experiences felt, particularly regarding premium taste, affordable price, and fast service, leading all customer informants to express willingness to repurchase and recommend D Kopi Paste to others. However, areas not yet strategically articulated by the owner were also identified, namely formal customer loyalty management and diversification of promotional channels beyond social media. The novelty of this research lies in its use of a two-way synchronization analysis framework (owner-perceived strategy versus customer-perceived experience) at the micro street-vendor MSME level, which has rarely been explicitly examined in MSME marketing literature in West Sumatra. This study offers practical contributions for similar MSME actors in designing evidence-based marketing strategies and theoretical contributions to the development of synchronization studies in MSME marketing rooted in Minangkabau local wisdom.